Ocean Energy: Markets – Currency – Impact. Dimension of & Choices in the Technology Development Space (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Reflecting in the acceleration of the changes in ecological, climatological and generally planetary health, it is critical to employ those energy source as well and those energy used that are of the highest ratio of benefit to effort and deliver the most valuable and impactful, tangible contribution in service of natural commons and common societal good. Such considerations hold for all ocean energy types and especially for ocean wave energy.Thus, it is not only important to consider the resource that is converted into the standard form of usable energy, that is, in the form of electricity and to deliver to the most prominent marketplace, that is, the continental grid; it is equally important to consider the use, purpose and impact after converted energy.Reflecting on the entire value chain from marine renewable energy to a) usable energy to b) the actual use and purpose of the energy may lead to highly impactful implementations with more direct delivery of the renewable energy to the valued application. In such more direct paths from resource to impact the extracted energy and the applied energy is a mean to the purpose rather than a means to an end.Assessments of marine renewable energy markets other than powering the continental grid, such as Powering the Blue Economy, have been investigated and numerous research efforts are underway. However, to fully maximize the achievable impact of ocean wave energy it is critical to extend the consideration from replacing the energy source in existing applications to the enablement of highly impactful applications that are currently not existing or are not operated at the magnitude when powered by ocean waves.Highest effectiveness is achieved when the uniqueness of the renewable energy form matches the unique needs of the targeted application. For ocean wave energy the uniqueness lies in relative consistency, high degree of forecastability, energy density and the ubiquitous nature across the oceans. These provide a plethora of opportunities to serve markets and purposes that are directly in or based on the oceans.Technology development progress indicators such as Technology Readiness Levels (TRL) and Technology Performance Levels (TPL) are typically used to span up the technology development space and provide a framework and orientation for the desired technology development trajectories. Based on the description of the motivations above the paper and presentation with introduce and describe additional and alternative technology development indicators that directly point and guide the development towards impactful application and purpose as the desired technology development goal. In order to provide a clear understanding of impact markets and the associated values, thus, their specific currency these are best served in, three impact markets are presented in detail as concrete examples.  These support planetary and ocean health in different ways through carbon capture, acceleration of the deployment of all forms of marine renewable energy types and enabling the implementation and enforcement of environmental legislation. Beyond these, a dozen of others impact markets are listed to provide an overview of impact oriented markets and applications.